Building locally led agricultural policy analysis capacity: Lessons from experience in developing countries - Jayne, Thomas S.; Babu, Suresh Chandra; Boughton, Duncan; Hendriks, Sheryl L.; Mkandawire, Elizabeth; Dorosh, Paul A.; Savadogo, Kimsey (Michigan State University, 2019)
Agricultural policies affect almost everyone in the world, directly or indirectly. Improvements in agricultural policy analysis capacity can therefore significantly benefit society. This report synthesizes lessons learned from the Food Security Policy Innovation Lab’s capacity strengthening efforts over the 2013–2018 period and from related capacity development initiatives conducted over the last four decades by the partner institutions in Africa and Asia. “Capacity” is defined as the resources required for people and institutions to reach their objectives and achieve results in an efficient and sustainable manner. Capacity development is therefore the process of enhancing, improving, and unleashing such resources—in people, organizations, and systems. In this report, the term “locally led” refers to institutions registered in the host country, led by nationals of the host country, and often, but not necessarily, affiliated with a public university or government unit in the host country. Why is the development of locally led agricultural policy analysis important? In principle, governments in developing countries could continue to receive policy analysis guidance from external research organizations, yet governments in most medium- and high-income countries rely on policy guidance from locally led research groups in their own countries. One lesson from capacity development initiatives is that governments are more likely to seriously listen to and engage with policy guidance provided by research units led by well-respected researchers in their own countries, who know the country, the culture, and the local politics surrounding agricultural policy issues. The impact of technical analysis and policy guidance cannot be divorced from policymakers’ trust and respect for the person/group providing it. For these reasons, well-functioning locally led policy analysis units play a crucial role in an effective policy environment, and they can raise the probability that policy analysis will contribute to policy impact. These points in no way downplay the importance of international research units—in fact, they must often play a crucial support role to raise the capacities of locally led policy analysis units to improve the quality of policy decisions in their countries.